2021
DOI: 10.1101/2021.01.04.425249
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intricate regulation of ribosome biogenesis genes in response to mTORC1 signaling

Abstract: SummaryGenes encoding ribosomal proteins are repressed in response to inhibition of mTORC1. In Saccharomyces cerevisiae, this involves dissociation of the activator Ifh1p in a process that depends on Utp22p, a protein that also functions in pre-rRNA processing. Ifh1p has a paralog, Crf1p, which can mediate mTORC1 inhibition by acting as a repressor. Ifh1p and Crf1p derive from a common ancestor, which may have acted as both an activator and a repressor. We report here that UTP22 and RRP7, which encodes another… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Regulation of HMO1 appears to be more complex. Rapamycin treatment does not lead to reduced HMO1 mRNA abundance in a W303-derived crf 1Δ strain, except under conditions of prolonged (>1h) exposure [105] . It is also notable that HMO1 mRNA abundance is not reduced as efficiently as RP genes (<50%) when wild-type cells are treated with rapamycin.…”
Section: A Role For Ifh1p and Crf1p At Non-rp Genesmentioning
confidence: 85%
See 4 more Smart Citations
“…Regulation of HMO1 appears to be more complex. Rapamycin treatment does not lead to reduced HMO1 mRNA abundance in a W303-derived crf 1Δ strain, except under conditions of prolonged (>1h) exposure [105] . It is also notable that HMO1 mRNA abundance is not reduced as efficiently as RP genes (<50%) when wild-type cells are treated with rapamycin.…”
Section: A Role For Ifh1p and Crf1p At Non-rp Genesmentioning
confidence: 85%
“…This experiment also showed that repression of Category I and II RP genes in response to rapamycin treatment is compromised when Crf1p entirely replaces Ifh1p [37] , consistent with absence of the N- and C-terminal protein domains in Crf1p, which have been implicated in removing Ifhl1p from RP gene promoters. Furthermore, we have recently reported that endogenous Crf1p also promotes expression of select Category I and II RP genes during balanced growth as evidenced by reduced mRNA accumulation in a crf 1Δ strain [105] . Taken together, these observations suggest that Crf1p functions as an activator.…”
Section: Rp Gene Regulation In Yeastmentioning
confidence: 98%
See 3 more Smart Citations